Enhancing Curing Methods for Cement Mortar: Integrating Self-Curing Agents for Better Performance - K Jayasankar; Krishnaraj, L; P T Ravichandran (International Journal of Sustainable Construction Engineering and Technology, 2024)
The work examines the early-age mortar properties in order to study the effect of self-curing agents and their possible application as internal curing agents. Some challenges in the curing of cement mortar include the influence of moisture loss and environmental conditions on mechanical integrity. The self-curing mortars, thus, seem to offer a way out by using additives that promote internal moisture retention for better performance and durability. This paper primarily discusses the effectiveness of SCA in mitigating capillary stress and autogenous shrinkage, with emphasis on the involvement of pore structure and water absorption during hydration in cements. The materials considered in this research include cementitious materials, while the curing agents are SAPS and two types of polyethylene glycols, namely PEGL and PEGP added at different concentrations. Compressive strength, water absorption, and other tests have been carried out on mortars cured in air and water for a period of 56 days. Results have indicated that 0.3% of SAPS, 1.0% of PEGL, and 1.0% of PEGP yield significantly higher compressive strength, especially under proper curing conditions. The water curing has higher strength compared to air curing in all cases; thus, curing is an important role player in the giving of properties to mortars. The present study concludes that self-curing mortars may present potential for sustainable construction but additives and curing conditions have to be carefully selected. The best performance from Table 6 was recorded for PEGL-modified PPC, and it is expected that reliance on traditional, labor-intensive external curing will be minimized by adopting self-curing methods to improve construction efficiency and sustainability.